OPTIMIZING TROUGH WITHERING PROCESS IN BLACK TEA MANUFACTURE - Chương, Đỗ Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARY Tea-withering technology by using withering trough was studied by applying experimental planning method (level 2). Optimum technical data for withering process, as a result, was identified i.e. hot air temperature, air flow rate supplying for the trough, and tea-withering time. The results can help factories totally avoid the casual withering by applying the technology in withering process to get better quality tea. Achieving the desired level of withering can create favourable conditions for next processing phases. This contributes to enhance and stablize the product quality. The results are also supplemented to textbooks on tea manufacturing techniques at universities, colleges, schools in the country.